Research on Design and Application of National Fitness System - Shengyou Wang (Journal of Mathematics)
In order to improve the physical quality of the national people, a national fitness system is designed and applied to practice. Design the overall architecture of the national fitness system, including the perception layer, network layer, and application layer. The perception layer mainly uses Internet of Things gateway, central machine, wireless perception node, and fitness data dashboard to obtain fitness data. The network layer mainly uses WiFi, 4G, Ethernet, and other public networks to transmit fitness data, fitness guidance data, and equipment operation and maintenance data. The application layer provides data storage, device management, user management, and client services. On this basis, through the collection of users’ fitness data rating data, the data are transformed into fitness data rating matrix, and the matrix is analyzed and calculated to realize the intelligent recommendation of fitness data and complete the design of national fitness data recommendation algorithm. The test results show that the system can meet the requirements of normal use, good compatibility, and user score is high and has high practical application value.